Pengembangan Buku Pintar Digital Berbantuan Canva pada Materi Kata Hubung, Huruf Kapital dan Tanda Titik Bahasa Indonesia Kelas II Sekolah Dasar - Ardinda, Lusi Ayu; Sari, Eka Yuliana; Syafi’ah, Rohmatus (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is motivated by the need for an attractive and easy-to-use digital learning media to help second-grade elementary school students understand the material on conjunctions, capital letters, and periods in learning Indonesian. This study aims to describe the development process, validity, and practicality of a digital smart book assisted by Canva. The study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of two media experts, two material experts, two linguists, teachers, and second-grade students of SDN 2 Tiudan, Tulungagung Regency. Data were collected through validation sheets and response questionnaires, then analyzed descriptively quantitatively using percentages. The results showed that the validation of media experts obtained an average of 98%, material experts 97.5%, and linguists 97%, all of which are categorized as very valid. Student responses obtained a percentage of 96% and teacher responses 96%, both of which are categorized as very practical. Thus, the digital smart book assisted by Canva is declared very valid and very practical to be used as a learning medium for Indonesian language for class II on the material of conjunctions, capital letters, and periods.